Going international: the challenges for the Brazilian Federal Institutes of Education, Science and Technology - Gicele Vergine Vieira; Kyria Rebeca Finardi Finardi; Gabriela Freire Oliveira Piccin (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
The present study assumes that, in a globalized world, the view of English as an international language and internationalization initiatives are essential to foster social capital and the circulation of academic production worldwide. The aim of this study is twofold: to offer a meta-summary analysis of some studies which investigated the internalization of Brazilian higher education carried out mostly in federal universities, and, based on this analysis, to draw considerations regarding the challenges faced by the Brazilian Federal Institutes of Education, Science and Technology (IFs) to go international. In order to do so, a meta-summary approach was used to appraise and synthesize the main findings of the five studies included in the synthesis. In addition, a semi-structured questionnaire was administered to two IFs representatives as an attempt to unveil which internationalization initiatives have been put into practice. Data of the questionnaire was analyzed qualitatively and a discussion is provided taking into account the nature of the programs and actions offered by these institutions to go international as well as the challenges they have faced so far.